Zygospores of the green alga Spirogyra: new insights from structural and chemical imaging - Permann, Charlotte; Gierlinger, Notburga; Holzinger, Andreas (Frontiers in Plant Science, 2022)
Zygnematophyceae, a class of streptophyte green algae and sister group to land plants (Embryophytes) live in aquatic to semi-terrestrial habitats. The transition from aquatic to terrestrial environments requires adaptations in the physiology of vegetative cells and in the structural properties of their cell walls. Sexual reproduction occurs in Zygnematophyceae by conjugation and results in the formation of zygospores, possessing unique multi-layered cell walls, which might have been crucial in terrestrialization. We investigated the structure and chemical composition of field sampled Spirogyra sp. zygospore cell walls by multiple microscopical and spectral imaging techniques: light microscopy, confocal laser scanning microscopy, transmission electron microscopy following high pressure freeze fixation/freeze substitution, Raman spectroscopy and atomic force microscopy. This comprehensive analysis allowed the detection of the subcellular organization and showed three main layers of the zygospore wall, termed endo-, meso- and exospore. The endo- and exospore are composed of polysaccharides with different ultrastructural appearance, whereas the electron dense middle layer contains aromatic compounds as further characterized by Raman spectroscopy. The possible chemical composition remains elusive, but algaenan or a sporopollenin-like material is suggested. Similar compounds with a non-hydrolysable character can be found in moss spores and pollen of higher plants, suggesting a protective function against desiccation stress and high irradiation. While the tripartite differentiation of the zygospore wall is well established in Zygnematopyhceae, Spirogyra showed cellulose fibrils arranged in a helicoidal pattern in the endo- and exospore. Initial stages of lipid peroxidation in mature zygospores, as well as incorporation of lipid bodies during early zygospore wall formation were observed, suggesting a key role of lipids in zygospore wall synthesis. Multimodal imaging revealed that the cell wall of the sexually formed zygospores possess a highly complex internal structure as well as aromatics, likely acting as protective compounds and leading to impregnation. Both, the newly discovered special three-dimensional arrangement of microfibrils and the integration of highly resistant components in the cell wall are not found in the vegetative state. The variety of methods gave a comprehensive view on the intricate zygospore cell wall and its potential key role in the terrestrial colonization and plant evolution is discussed.